An empirical analysis of volatility in South African oil prices - Mofema, Victor Mbua; Mah, Gisele (Journal of Energy in Southern Africa, 2021)
Volatility of the oil price has been around since the 1970s and an understanding of how it evolves provides insight into solving macroeconomic challenges. The main objective of this study was to analyse the volatility of South African oil prices using quarterly time series data from 2000 to 2020. The effect of growth in gross domestic product per capita, interest rate, inflation and money supply growth on oil price changes was assessed. Generalised autoregressive conditional heteroscedasticity (GARCH) was estimated and diagnostic tests – namely ARCH, normality and autocorrelation tests – were conducted. The GARCH (1,2) model was the best fit, based on the Alkaike information criterion. The result revealed that interest rates and money supply growth have a significant positive effect on oil price changes in South Africa, while growth in GDP per capita and inflation has an insignificant impact. Past one and two-quarters’ oil price volatility increases and decreases the current oil price volatility respectively. Based on the findings, a contractionary monetary policy is recommended in order to reduce the volatility of South African oil prices.